The Revitalization of Women’s Entrepreneurship Spirit In Micro Enterprises With Islamic Microfinance Institution (IMI) (Study on The Contribution of BMTs Agam Madani in Agam sub-province, West Sumatra) - Hesi Eka Puteri (Tazkia Islamic Finance and Business Review, 2013)
Objective - The objective of this paper is to give an overview of the contribution of Islamic Microfinance Institutions (IMI) in the process of empowerment of women microenterprises, and recommended a related policy.Method – This study is a field research in 2012, which focused in BMTs Agam Madani at Agam district. The data is sourced from the observation, documentation and questionnaires from 60 women micro-entrepreneurs samples who receive working capital financing. This paper uses simple regression model in order to observe relationship between working capital and the increasing of revenue. This model is to measure the amount of the multiplier effect in working capital-to increasing of revenue.Result – This paper found that IMI is a good model to develop society more prosperous by developing BMTs in each district. These BMT has thousands of micro enterprises member and could revitalized the spirit of entrepreneurship of minangkabau’s women. A research to 60 women’s micro entrepreneur samples showed the positive significant influence between lending to revenue. A multiplier effect equal to 0.068.The small number of multiplier effect implied that many factors determining their revenue, not lending only.Conclusion – This finding could explain that IMI could empower micro entrepreneur woman. This finding also recommend few strategies: 1) Revitalization of BMTs as micro catalyst by revitalization of structure of organization, products variation, human resource compentence, sharia monitoring, public cooperation and implementating local cultural value 2) Revitalization of government role as fasilitator, coordinator, initiator and mediator in developing micro sector. Keywords : Women’s Entrepreneurship, Micro Enterprises, Islamic Microfinance Institution, BMTs Agam Madani